Student Character Education Building on Biology Learning Through the Scientific Approach - Purnama, Dirga; Hasruddin, Hasruddin; Aryeni, Aryeni (FMIPA UNNES, 2019)
The purpose of this study was to evaluate character education in students with the implementation of a scientific approach based on curriculum 2013 in the field of biological studies. The characters studied are related to honesty, discipline, cooperation, and independence of student. This descriptive study used 146 students at SMAN 1 Tebingtinggi as sample which were determined by random sampling techniques. Data was collected by questionnaire, 7 questions were about honesty, 8 questions were about discipline, 8 questions were questions about collaboration, and 7 questions were about independence. Data was analyzed by percentage technique. The results of the study showed that honest characters was at an average score of 2.73 (sufficient), the character of the discipline was at an average score of 3.11 (good), the character of cooperation was at an average score of 2.73 (enough), and independent characters was at an average score of 2.68 (enough).